2022
DOI: 10.3390/ijerph19020988
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a New AMCOP® Elastodontic Protocol for Orthodontic Interceptive Treatment: A Case Series and Literature Overview

Abstract: Background: Elastodontics is a specific interceptive orthodontic treatment that uses removable elastomeric appliances. They are functional appliances that produce neuromuscular, orthopedic and dental effects. Thus, these devices are useful in the developmental age, when skeletal structures are characterized by important plasticity and adaptation capacity, allowing to remove factors responsible for malocclusions. Elastomeric devices are generally well tolerated by patients requiring simple collaboration and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…The digital workflow allows for a 3D scan of the dental arches and the design of tooth movements. It is possible to choose which teeth to move individually, as if using a segmented orthodontic system, or to move all the teeth simultaneously, as if using a straight wire or functional orthodontic system [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The digital workflow allows for a 3D scan of the dental arches and the design of tooth movements. It is possible to choose which teeth to move individually, as if using a segmented orthodontic system, or to move all the teeth simultaneously, as if using a straight wire or functional orthodontic system [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques range from administering biological molecules to innovative physical stimulation technologies [ 27 , 28 , 29 ]. In particular, prostaglandins exogenous application influences bone remodelling and accelerates tooth movement; however, these agents increase the risk of root resorption and pain [ 30 , 31 , 32 , 33 , 34 ]. Other studies have shown how the administration of other agents, such as epidermal growth factor (EGF), parathyroid hormone (PTH), 1.25 dihydroxyvitamin D3, and osteocalcin, accelerate the effects; however, their safety and efficacy in humans need to be further proven [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since many variables affect the recovery of an included tooth in a child after removing the supernumerary elements or the odontoma, most studies believe orthodontic treatment is necessary rather than waiting for the spontaneous eruption [8,25,34].…”
Section: Introductionmentioning
confidence: 99%